2006
DOI: 10.1038/sj.jid.5700348
|View full text |Cite
|
Sign up to set email alerts
|

Complete Maternal Isodisomy of Chromosome 3 in a Child with Recessive Dystrophic Epidermolysis Bullosa but No Other Phenotypic Abnormalities

Abstract: The mechanobullous disease Hallopeau-Siemens recessive dystrophic epidermolysis bullosa (HS-RDEB) results from mutations in the type VII collagen gene (COL7A1) on chromosome 3p21.31. Typically, there are frameshift, splice site, or nonsense mutations on both alleles. In this report, we describe a patient with HS-RDEB, who was homozygous for a new frameshift mutation, 345insG, in exon 3 of COL7A1. However, sequencing of parental DNA showed that although the patient's mother was a heterozygous carrier of this mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…UPD has been implicated in a number of genodermatoses, including Netherton syndrome, junctional epidermolysis bullosa and RDEB . By contrast, the occurrence of de novo microdeletion in an autosomal recessive disorder is extremely rare, and to the best of our knowledge, this event has only been reported once for RDEB, when Titeux et al .…”
Section: Discussionmentioning
confidence: 94%
“…UPD has been implicated in a number of genodermatoses, including Netherton syndrome, junctional epidermolysis bullosa and RDEB . By contrast, the occurrence of de novo microdeletion in an autosomal recessive disorder is extremely rare, and to the best of our knowledge, this event has only been reported once for RDEB, when Titeux et al .…”
Section: Discussionmentioning
confidence: 94%
“…Specifically, a recent report described a patient with HS-RDEB who was homozygotic for a novel frameshift mutation, 345insG, in exon 3 of COL7A1. 67 However, sequencing of parental DNA showed that although the patient's mother was a heterozygotic carrier of this mutation, the father's DNA contained only the wild-type sequence. Microsatellite analysis confirmed paternity, and genotyping of the entire chromosome 3 by microsatellite markers showed that the affected child was homozygotic for every marker tested, which originated from a single maternal allele in chromosome 3.…”
Section: Consequences Of Splice-junction Mutationsmentioning
confidence: 99%
“…Recently, studies comparing constitutional and tumour DNA genotypes revealed that UPD occurs in a variety of tumour types including neuroblastomas (Carén et al, 2008), clear cell renal carcinomas (Toma et al, 2008), pancreatic adenocarcinomas (Harada et al, 2008) and breast cancer (Murthy et al, 2002; Tuna et al, 2010) with most studies being performed on haematological malignancies (Fitzgibbon et al, 2005; Flotho et al, 2007; Mullighan et al, 2007; Radtke et al, 2009; Walter et al, 2009; Bullinger et al, 2010) (Figure 3). These studies have revealed that UPD can occur in almost any chromosome, but it is becoming evident that UPDs are non‐randomly distributed with cooperation occurring between the acquired UPD and gene mutations.…”
Section: Common Copy Number Neutral Loh Regions In Cancermentioning
confidence: 99%
“…Known homozygous mutated tumour suppressor or oncogenes are labelled in black and imprinted genes mapping to common regions of UPD are labelled in red. (Data taken from Lips et al, 2007; Tuna et al, 2010; Midorikawa et al, 2006; Walter et al, 2009; Fitzgibbon et al, 2005; Bullinger et al, 2010.)…”
Section: Common Copy Number Neutral Loh Regions In Cancermentioning
confidence: 99%